Deskripsi Faktor-Faktor Penyebab Perawat Tidak Menghentikan Kebiasaan Merokok - Fitria Indah Sari; Ari Pristiana Dewi; Gamya Tri Utami (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
The purpose of this research was to identify the cause factors among nurses who cannot stop their smoking habit. This research used a simple descriptive. The sample of this research werenurses at Arifin Achmad Hospital, the total number of samples was 56 respondents who were taken byaccidental sampling technique. Instruments in this researchused questionnaire with 30 questions that had been tested for validity and reliability which was r count >r table 0,444. Data analysis used univariate analysis which are presented in the frequency distribution table. The results showed thatneeds, relationships, addiction, ignorance, motivation and anxiety were variable factors that causing indifference why nurses do not stop smoking, which ignorance was highest. Based on these results, it is expected that nurses who have the habit of smoking can behave healthy lifestyle, including donot smoking. Keywords: addiction,anxiety, ignorance,cigarettes,motivation, needs, relationships, nurse